2000
DOI: 10.1073/pnas.97.14.7732
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of human stem cell factor: Implication for stem cell factor receptor dimerization and activation

Abstract: Stem cell factor (SCF) plays important roles in hematopoiesis and the survival, proliferation, and differentiation of mast cells, melanocytes, and germ cells. SCF mediates its biological effects by binding to and activating a receptor tyrosine kinase designated c-kit or SCF receptor. In this report we describe the 2.3-Å crystal structure of the functional core of recombinant human SCF. SCF is a noncovalent homodimer composed of two slightly wedged protomers. Each SCF protomer exhibits an antiparallel four-heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 49 publications
(49 reference statements)
7
93
1
3
Order By: Relevance
“…Structural analyses of SCF dimers have shown that complex formation between the two SCF protomers is mediated by a large interface involving primarily hydrophobic interactions (8,9). Moreover, on KIT binding, the angle between the two SCF protomers is altered by ∼5° (10, 11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural analyses of SCF dimers have shown that complex formation between the two SCF protomers is mediated by a large interface involving primarily hydrophobic interactions (8,9). Moreover, on KIT binding, the angle between the two SCF protomers is altered by ∼5° (10, 11).…”
Section: Resultsmentioning
confidence: 99%
“…Structural and biochemical studies have shown that the N-terminal region composed of D1, D2, and D3 of KIT extracellular region functions as a binding site for SCF, which, by virtue of its homodimeric structure, is responsible for bringing about KIT dimerization (6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…The soluble protein is heavily N-and O-glycosylated, has extensive secondary structures and is dimeric (non covalently associated) under non-denaturating conditions (Arakawa et al, 1991;Langley et al, 1992;Zhang et al, 2000). The presence or absence of the carbohydrate moieties does not influence the biological activity (Flanagan and Leder, 1990;Zsebo et al, 1990), whereas the two intramolecular disulfide bonds of SCF are essential (Jones et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These processes occur through activation of KIT upon binding by stem cell factor (SCF), a ligand found in membrane-anchored and soluble forms (1,2) in a variety of cell types, including hematopoietic stem cells, germ cells, vascular endothelial cells, and the mesenchymal cells with uniquely neuromuscular differentiation known as the interstitial cells of Cajal (3,4). KIT belongs to the type III subfamily of RTKs (5), a family composed of an extracellular region that includes five Ig-like domains (designated D1-D5), a single transmembrane domain (TM), a juxtamembrane region (JM), a tyrosine kinase domain split by a kinase insert, and a C-terminal tail (6) (Fig.…”
mentioning
confidence: 99%